STRUCTURE AND DYNAMICS OF ZOOPLANKTON COMMUNITIES IN KARAKALPAKSTAN (Proceedings of International Educators Conference, 2024)
The peculiarity of this study is that hydro biological monitoring of lakes was carried out against the background of their progressive shallowing, which was accompanied by a reduction in the lakes’ water area and an accelerated increase in water mineralization.